COMPARISON OF AN ALTERNATIVE TECHNIQUE WITH THE STANDARD METHOD FOR THE DIAGNOSIS OF CARPAL TUNNEL SYNDROME - Haydar Gök; Saime Ay; Şehim Kutlay; Yeşim Kurtaiş Gürsel (Archives of Rheumatology, 2003)
We aimed to determine the normal range of latency difference between second lumbrical (2L) and interossei (INT) muscles and to compare with standard electrophysiologic technique for the diagnosis of carpal tunnel syndrome (CTS) in this study. 100 patients complaining of pain and paresthesias in their hands were included in the study. Control group consisted of 48 healthy individuals. All of the patients were undergone standard electrophysiologic evaluation for the diagnosis for CTS. Using alternative technique, we evaluated the difference between the distal motor latencies of INT and 2L muscles in 42 patients diagnosed as CTS and 48 healthy controls according to the standard technique. Sensitivity and specifity of 2L-INT latency differece in the diagnosis of CTS were found to be high. It was concluded that due to involvement of 2L fibers as much as abductor pollicis brevis motor fibers, 2L-INT latency difference can be used as an alternative technique to the standard method in the diagnosis of CTS.